ETPOD (European Training Program on Organ Donation): a successful training program to improve organ donation. (31st December 2012) - Manyalich, Marti; Guasch, Xavier; Paez, Gloria; Valero, Ricard; Istrate, Melania
Summary: Advanced training of healthcare professionals active in organ donation is highlighted as a major means to overcome organ shortage. The objective of this study was to improve donation rates in the selected European target areas (TAs) by providing an advanced training program. A prospective intervention study was conducted in 25 TAs with active donor programs from 17 European countries, between 2007 and 2009. A training program based on collaborative methodology was designed at three different professional levels (health workers awareness, junior transplant coordinators, managers). Courses evaluation scores and donation figures in each TA were collected and compared before and after intervention. Courses with new developed training tools were implemented reaching out 3286 healthcare professionals. Feed‐back questionnaires revealed a high degree of satisfaction among participants (average of 4.35 on a 1–5 scale). The number of utilized donors in the TAs increased from 15.7 ± 14.3 (95% CI: 9.8–21.6) to 20.0 ± 17.1 (95% CI: 13–27.1) ( P  =   0.014) and the number of organs recovered increased from 49.7 ± 48.5 (95% CI: 29.6–69.7) to 59.3 ± 52.1 (95% CI: 37.8–80.8) ( P  = 0.044). The European Training Program on Organ Donation is a successful training program, achieving a significant increase in organ donation figures.